Analysis of Physical Evidence and Promotion of Braga Tourism Village on the Interest in Visiting Tourists - Oktaviani, Desy; Sukma, Andhi; Latifah, Ifa; Al Hafidz, Salma Nur (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Interest in visiting is an encouragement that arises from within each individual to visit a tourist attraction. Interest in visiting tourists to a tourist attraction is influenced by several factors such as physical evidence and promotions carried out by the manager. If the value of physical evidence and promotional activities is increased, then tourist visits will also increase to a tourist attraction. This study aims to determine the effect of physical evidence and promotion on Tourist Interest in Braga Tourism Village in Bandung City. This study uses quantitative methods with descriptive analysis and verification approaches. The population of this study were prospective tourists who would visit the city of Bandung. The data that has been collected and obtained from the results of this study was then calculated using the SPSS ver. 25 application. 25. From the results of this test, it can be concluded that physical evidence has a significance value of 0.038 less than 0.05 so it can be concluded that it has a positive and significant influence on visiting interest. Promotion also has a significance value of 0.000 less than 0.05 so it can be concluded that the promotion variable has a significant effect on tourist interest.